Edge dislocations in Ni monocrystalline structure studied by McChasy 2.0 Monte Carlo code. Issue 1 (1st October 2022) - Mieszczynski, Cyprian; Nowicki, Lech; Skrobas, Kazimierz; Jozwik, Przemyslaw; Jagielski, Jacek
Abstract: The main goal of the McChasy code, in general, is to reproduce Rutherford Backscattering Spectrometry experimental spectra recorded in channeling direction (RBS/C) by simulating He-ions travelling inside crystalline structures and to calculate the probability of the backscattering process. The 2.0 version of the code provides the possibility to simulate channeling spectra in large (ca. 10 8 atoms) arbitrary structures that are created based on crystallographic data or Molecular Dynamic (MD) calculations. In this work, we present the current status of the code and the results of recent investigations of extended structural defects (edge dislocations and dislocation loops) formed inside nickel (Ni) single crystals. Two ways of modelling extended defects are described: one developed using the McChasy code (Peierls-Nabarro approach) and the other one obtained by modification and thermalization of Ni structures by MD (LAMMPS code). The atomic local environment was studied qualitatively and quantitatively by the local projectile-flux density distributions around the defects.